Global Influence and Local Adaptation: The Integration of English in Chinese Internet Slang - Kuszel, Bartlomiej (Ilmu Inovasi Nusantara, 2025)
This study explores the influence of English on Chinese internet slang, focusing on how English-derived acronyms, morphemes, and code-switching have become integrated into online Chinese discourse. Although China is typically categorized as a low-proficiency English environment, many elements originating from English continue to enter Chinese social media, creating hybrid forms. This study aims to investigate how English lexical and morphological elements are localized, repurposed, and recontextualized by Chinese netizens on social platforms such as WeChat, Douyin, and Xiaohongshu. The method used in this study is discourse analysis, with data collected from various posts and comments on these platforms. The results indicate that, despite English not being the primary language in China, the use of English elements in internet slang is increasingly growing, reflecting a creative adoption that is localized according to Chinese culture and social norms. Elements such as acronyms and code-switching are used to express emotions, humor, and group identity, demonstrating the significant impact of global influences on online communication. Based on these findings, it is recommended that further research focus on the influence of social media in the formation of new languages and the relationship between language globalization and local culture, as well as its impact on the language proficiency of China's younger generation